2016
DOI: 10.1016/j.socscimed.2016.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Association of neighborhood context with offspring risk of preterm birth and low birthweight: A systematic review and meta-analysis of population-based studies

Abstract: Findings from studies investigating associations of residential environment with poor birth outcomes have been inconsistent. In a systematic review and meta-analysis, we examined associations of neighborhood disadvantage with preterm birth (PTB) and low birthweight (LBW), and explored differences in relationships among racial groups. Two reviewers searched English language articles in electronic databases of published literature. We used random effects logistic regression to calculate odds ratios (and 95% conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
153
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(170 citation statements)
references
References 102 publications
7
153
1
3
Order By: Relevance
“…7-17 Results from a recent meta-analysis, which included three studies focused on AAs, all of which used vital statistics data, suggested modest positive associations, with a stronger relationship among Whites compared to AAs. 17 However, limitations of using vital statistics data include inaccurate reporting of clinical information including gestational age, and that the data is collected for public health surveillance, rather than to answer specific clinical or population-based research questions. 18 …”
Section: Introductionmentioning
confidence: 99%
“…7-17 Results from a recent meta-analysis, which included three studies focused on AAs, all of which used vital statistics data, suggested modest positive associations, with a stronger relationship among Whites compared to AAs. 17 However, limitations of using vital statistics data include inaccurate reporting of clinical information including gestational age, and that the data is collected for public health surveillance, rather than to answer specific clinical or population-based research questions. 18 …”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with several other studies on adverse birth outcomes and neighborhood-level risk factors, such that neighborhood effects among Black women are greater and more variable than among White women. 13 A possible explanation for the small within racial group difference could be due to unmeasured confounding among Whites, such that observable differences in high domestic violence and low domestic violence neighborhoods on SGA births were minimized 7,11 . Nonetheless, findings on neighborhood-level risk factors and adverse birth outcomes remain inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…3–5 Efforts to understand why risk differences persist are increasingly focused on broader, contextual factors beyond individual characteristics, with the understanding that the environment in which people live, work, and grow can influence health. 6–11 Previous explorations of neighborhood-level determinants of adverse birth outcomes have predominantly focused on socioeconomic indicators such as poverty and unemployment rates, median household income, and the concentration of economic disadvantage that occurs in racially segregated areas. 9,12 While area-level socioeconomic disparities have been consistently associated with adverse birth outcomes, socioeconomic conditions alone fail to capture the multiple ways in which neighborhood context influences racial disparities in women’s health, 10,13 and there is a need to better understand the mechanisms through which neighborhood conditions may impact birth outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leventhal & Brooks-Gunn, 2004). Much work reports that women living in disadvantaged neighborhoods are more likely to deliver infants preterm or low birth weights (Culhane & Elo, 2005; Margerison-Zilko et al, 2015; Masi, Hawkley, Piotrowski, & Pickett, 2007; Morenoff, 2003; Ncube, Enquobahrie, Albert, Herrick, & Burke, 2016; O’Campo et al, 2008; Vos, Posthumus, Bonsel, Steegers, & Denktas, 2014), suggesting possible intergenerational effects of neighborhood context, whereby the influence of disadvantaged environments on child health begins in utero or prior to conception. A small body of research has examined the specific pathways by which early-life neighborhood exposures influence children’s health.…”
Section: Empirical Reviewmentioning
confidence: 99%